Compassionate conversations in architecture: An educational experiment in the field of adaptive reuse - Hannes, Els (EAAE Annual Conference Proceedings, 2025)
This paper reports the outcomes of an educational experiment (set-up, execution and evaluation) in the master program ‘Adaptive Reuse’ and exchange programs at the faculty of Architecture and Arts of Hasselt University in Belgium during the first semester of 2023-2024. The framework of “non-violent com- munication” (NVC), also called “compassionate communication”, as developed by Rosenberg was introduced to a mixed group of 32 international students. The aim was to improve their intercultural communication skills while building a frame of reference in adaptive reuse. Students learn how to use NVC as a lens for human interaction and for spatial transformation projects simultaneously. The paper explains NVC and its relevance to (interior) architects. Next, it reports how NVC was introduced gradually in consecutive classes and field assignments of the “Study Visits” course. Some results are highlighted, and a critical evaluation is shared. The paper concludes that linking NVC principles with architectural language seems to enhance (interior) architecture students’ understanding of NVC as such, and raise awareness regarding their ability to actively contribute to empatic design.